Synthesis of novel heterocyclic systems as potential inhibitors of HIV-1 enzymes - Sekgota, Khethobole Cassius (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
This study has focussed on the application of Baylis-Hillman methodology in the development of efficient synthetic pathways to libraries of novel 3-[(N-cycloalkylbenzamido)methyl]-2-quinolones and indolizine-2-carboxamides and on an exploration of their medicinal potential. The approach to 3-[(N-cycloalkylbenzamido)methyl]-2(1H)-quinolones involved a six-step pathway comprising: Baylis-Hillman reaction of 2-nitrobenzaldehyde derivatives and methyl acrylate to afford nitro-Baylis-Hillman adducts; thermal cyclisation of the adducts to give a range of 3-(acetoxymethyl)-2(1H)-quinolones in good to excellent yields; hydrolysis of the acetates; conversion of the resulting alcohols to the 3-chloromethyl analogues; amination; and, finally, acylation to afford the target amides. Variable temperature NMR methods were used to facilitate analysis of the Â¹H and Â¹Â³C NMR spectra which were complicated by internal rotation and cycloalkyl ring-flipping effects. On the other hand, the indolizine-2-carboxamides were obtained in several steps commencing with the Baylis-Hillman reaction of pyridine-2-carboxaldehyde and methyl acrylate. Thermal cyclisation of the Baylis-Hillman adduct afforded indolizine esters, hydrolysis of which gave the corresponding acids which served as precursors to the target indolizine-2-carboxamides. The final amidation step, however, proved to be particularly challenging. Various coupling strategies were explored to access indolizine-2-carboxamides. These included the use of 2,2,2-trifluoroethyl borate which showed limited promise, but propylphosphonic acid anhydride (T3P) proved to be the most effective coupling agent, permitting the formation of 24 novel indolizine-2-carboxamides from hydrazines, aliphatic amines and a range of heterocyclic amines. A high-field NMR-based kinetic study of the mechanism of the Baylis-Hillman reaction of pyridine-4-carboxaldehyde and methyl acrylate in the presence of 3-hydroxyquinuclidine in deuterated chloroform was initiated, reaction progress being followed by the automated collection of Â¹H and DEPT 135 NMR spectra over ca. 24 hours using a high-field (600 MHz) NMR instrument. The results have provided critical new insights into the mechanism. NMR analysis has also been used to elucidate the multiplicity of signals associated with rotameric equilibria observed at ambient probe temperature. Variable temperature 1D- and 2D-NMR spectra were used to facilitate the unambiguous characterisation of the 2-quinolone benzamides and some of the indolizine-2-carboxamides. The 3-[(N-cycloalkylbenzamido)methyl]-2(1H)-quinolones, together with selected precursors, and a number of the indolizine-2-carboxamides have been screened in vitro as potential HIV-1 enzyme inhibitors. A survey of the activity of the 2-quinolones against HIV-1 integrase, protease and reverse transcriptase revealed selective inhibition of HIV-1 integrase with the most active IN inhibitor, 3-[(cyclopentylamino)methyl-6-methoxy-2(1H)-quinolone 115e, producing residual enzyme activity of 40% at a concentration of 20 Î¼M. Many of the 2-quinolones exhibited no significant cytotoxicity against HEK 293 cells at 20 Î¼M concentrations. 3-[(N-Cyclohexylamino)methyl]-6-methoxy-2(1H)-quinolone 114e was the only compound to exhibit ant-plasmodial activity (55% pfLDH activity). The survey of indolizine-2-carboxamides also revealed encouraging inhibition against HIV-1 integrase. None of these compounds exhibited cytotoxicity at 20 Î¼M against HEK 293 cells, while a number of them exhibited some activity against Plasmodium falciparum (3D7 strain) and Trypanosoma brucei. Selected indolizine-2-carboxamides exhibited significant anti-tubercular activity in the 7H9 CAS GLU Tx and 7H9 ADC GLU Tw media. In view of the inherent fluorescent character and biological potential of the synthesised indolizine-2-carboxamides, their photophysical properties were explored to establish their possible dual use as bio-imaging and therapeutic agents. The major absorption and corresponding emission bands, and the associated molar absorption coefficients (Æ ) expressed in the form of log Æ were determined. Their high extinction coefficients, large Stokes shift and red-shifted emissions in the visible region indicate their potential for use as fluorophores.
Keywords: Protease inhibitors; Heterocyclic compounds; HIV (Viruses); Quinoline; Amides; Nuclear magnetic resonance; Antiretroviral agents; AIDS vaccines; Nitrobenzaldehyde; Propylphosphonic acid anhydride